Hubungan Perubahan Dividen Dengan Perubahan Laba Perusahaan Terdaftar Di Bei - Rendy Johan Gultom (Universitas Prasetiya Mulya, 2017)
This research aims to analyze the relation between dividend changes with earnings changes of the employee listed on Indonesia Stock Exchange (BEI) also to determine whether the dividend changes could predict the earnings changes. This study conducts two tests with two different research periods: during 2004 – 2006 and 2006 – 2008. The result of the research proves that dividend changes has a relationship with company’s earnings changes in the future. From the test with two different research periods, shows that there is a negative correlation between dividend changes with earnings changes a year after dividend changes. This research also finds that dividend changes could predict earnings changes one year after dividend changes. Keywords: dividend changes, earnings changes, Indonesia Stock Exchange (BEI) https://doi.org/10.21632/saki.1.1.72-93